Nitric oxide function in plant biology: a redox cue in deconvolution. Issue 4 (10th March 2014) - Yu, Manda; Lamattina, Lorenzo; Spoel, Steven H.; Loake, Gary J.
Summary: Nitric oxide (NO), a gaseous, redox‐active small molecule, is gradually becoming established as a central regulator of growth, development, immunity and environmental interactions in plants. A major route for the transfer of NO bioactivity is S‐nitrosylation, the covalent attachment of an NO moiety to a protein cysteine thiol to form an S‐nitrosothiol (SNO). This chemical transformation is rapidly emerging as a prototypic, redox‐based post‐translational modification integral to the life of plants. Here we review the myriad roles of NO and SNOs in plant biology and, where known, the molecular mechanisms underpining their activity. Contents Summary 1142 I. Introduction 1142 II. Routes of NO production 1143 III. Oxidative routes of NO synthesis 1143 IV. Reductive routes of NO synthesis 1144 V. Transfer of NO bioactivity 1144 VI. NO function in plant immunity 1145 VII. Role of NO in hypersensitive cell death 1147 VIII. NO and abiotic stress 1148 IX. NO function in plant development 1149 X. NO contributes to the balancing of growth with development in roots 1149 XI. NO action in root hair development and gravitropic responses 1151 XII. Signalling cross‐talk in roots between NO and ROIs 1151 XIII. NO regulation of root iron homeostasis 1152 XIV. Future perspectives 1152 Acknowledgements 1153 References 1153